Impaired Self-Referential Cognitive Processing in Bipolar Disorder: A Functional Connectivity Analysis - Zhang, Jian; Liu, Tiantian; Shi, Zhongyan; Tan, Shuping; Suo, Dingjie; Dai, Chunyang; Wang, Li; Wu, Jinglong; Funahashi, Shintaro; Liu, Miaomiao (Frontiers in Aging Neuroscience, 2022)
Bipolar disorder patients have deficits in self-referenced information. The brain functional connectivity during social cognitive processing in bipolar disorder is unclear. Electroencephalography was recorded in 23 patients with bipolar disorder and 19 healthy comparison subjects. We analyzed the time-frequency distribution of EEG power for each electrode associated with self, other and font reflection conditions and used the phase lag index to characterize the functional connectivity between electrode pairs for 4 frequency bands. Then, the network properties were assessed by graph theoretic analysis. The results showed that bipolar disorder induced a weaker response power and phase lag index values over the whole brain in both self and other reflection conditions. Moreover, the characteristic path length was increased in patients during self-reflection processing, whereas the global efficiency and node degree were decreased. In addition, when discriminating patients from normal controls, we found that the classification accuracy was high. These results suggest that patients have an impeded integration of attention, memory, and other resources of the whole brain, resulting in a deficit of efficiency and ability in self-referential processing.